Effects of temperature on drying of selected medicinal plants: drying time and product quality - Mohd Shahidan M A. (Forest Research Institute Malaysia, 2015)
The medicinal plants selected for this study are Orthosiphon aristatus and Chromolaena odorata which are known as Misai Kucing and Pokok Kapal Terbang in Malaysia. These plants are reported to contain various beneficial bioactivities. In herbal processing, fresh plants are normally dried before further processing to prevent chemical degradation and fungi infection. The drying process of herbs is strongly affected by drying temperature. This work studied the effects of drying temperature on drying time of these plants and the product quality. Kinetics data of the drying process was collected to determine the drying time required to achieve the required moisture content. Total flavonoids analysis was used to determine the change of product quality under different drying temperatures. The results indicate that the total flavonoids content in Chromolaena odorata decreased with the increase of drying temperature while a different trend was observed in Orthosiphon aristalUs.